STUDY OF PHENOLOGICAL PHASES OF QUINCE VARIETIES IN THE SOIL AND CLIMATIC CONDITIONS OF KARAKALPAKSTAN - Ruslan Baxitovich Seilbekov; Jasmina Kamalovna Kurbaniyazova (Web of Journals Publishing, 2025)
The phenological phases of the quince varieties “Samarkandskaya krupnoplodnaya” (st), “Aromatnaya”, “Izobelnaya”, “Mushk behi”, “Savkhoznaya”, “Krimskaya aromatnaya”, “Otlichnitsa” the introduced varieties “Anjerskaya”, “Grushavidnaya”, “Zakatolskaya”, “Konservnaya”, “Micha urojaynaya”, “Nagibrin”, “Tursh Bukharskaya” and the folk selection varieties “Non behi”, “Nordon” were studied. As a result of the study, it was found that the period from budding to the end of the growing season of trees lasted from 200 to 225 days.